2020
DOI: 10.1017/s0014479720000034
|View full text |Cite
|
Sign up to set email alerts
|

Parthenium weed (Parthenium hysterophorus) competition with grain sorghum under arid conditions

Abstract: Parthenium weed is an invasive species in a growing number of countries where it infests numerous crop fields, including sorghum. Two field studies were conducted to quantify the effect of parthenium weed on the performance of grain sorghum at different weed densities (0, 5, 10, 15 and 20 plants m−2) and durations of weed-crop competition (season-long weed-free, weed-free after 2, 4, 6 or 8 weeks, and season-long weedy). Our aim was to identify the density threshold and ideal duration to control parthenium wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…The negative correlation between weed density and growth components of okra corroborates previous reports that increasing weed density reduces crop growth (Ayodele 2021;Bajwa et al 2020). Also, Okayi et al (2017) reported a reduction in plant height, number of leaves and plant weight of okra with increasing density of tick weed (Cleome viscosa).…”
Section: Discussionsupporting
confidence: 88%
“…The negative correlation between weed density and growth components of okra corroborates previous reports that increasing weed density reduces crop growth (Ayodele 2021;Bajwa et al 2020). Also, Okayi et al (2017) reported a reduction in plant height, number of leaves and plant weight of okra with increasing density of tick weed (Cleome viscosa).…”
Section: Discussionsupporting
confidence: 88%
“…This prediction is not surprising, as other studies reported a massive reduction in the biomass of grain sorghum due to competition with P. hysterophorus in Ethiopian dryland. Such heavy loss occurs even at low densities of P. hysterophorus, e.g., five plants m -2 (Bajwa et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, parthenium weed infestations have been linked to significant yield losses in major field crops such as sorghum, maize (Zea mays L.), and rice (Oryza sativa L.) [15][16][17][18]. A recent study by Bajwa et al [19] reported a grain yield reduction of up to 81% in sorghum due to competition from parthenium weed in Pakistan. Similarly, Tamado et al [15] documented grain yield losses of up to 97% in sorghum due to severe parthenium weed infestations in arid conditions of Ethiopia.…”
Section: Introductionmentioning
confidence: 99%